Threads of Socio-pragmatics in Higher Education: Perspectives on Improving EFL Learning and Use - Hamoudi, Aboubakr (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
Research into language and social rapport connectedness has jumped to the fore in light of today’s internationalization of EFL pedagogy. Pertinence in daily ritualistic behaviors is problematic in social spaces where pragmatics of communities meet and grapple with each other. Socio-pragmatics has then gained speed as a method to approach EFL instruction and usage. This paper attempts to reveal EFL teachers and students’ consciousness levels of socio-pragmatics. It also assesses the adequacy of teachers’ socio-pragmatics-based instruction as well as the appropriateness of students’ socio-pragmatic performance. To attain those objectives, the researcher devised and distributed two questionnaires and a Written Discourse Completion Task (WDCT) on a sample of 100 EFL students and 18 tutors at M’sila University, Algeria. Findings indicate that students held insufficient awareness and scored poorly in the performance test of socio-pragmatics. Although teachers demonstrated high consciousness levels, their socio-pragmatic instruction was very limited in the context of teaching. Relative deficiency at the levels of socio-pragmatics’ instruction, awareness and/or performance perpetuates communicative problems to take form in EFL discourse. Thus, socio-pragmatics constitutes a method as well as a content-ridden construct that is of particular attention to infuse EFL higher education with efficiency and success.